DAMPAK INTENSITAS PENGGUNAAN SMARTPHONE TERHADAP MINAT BACA PESERTA DIDIK: THE IMPACT OF SMARTPHONE USE INTENSITY ON STUDENTS' READING INTEREST - Heriady; Anhar (Jurnal Risalah Addariyah: Studi Ilmu-Ilmu Keislaman, Pendidikan dan Sosial Kemasyarakatan, 2022)
The use of smartphones in the current digital era has many positive and negative impacts on students. Therefore, it is necessary to use rules that are right on target so that they do not have implications for students' reading interests. The purpose of this research is to describe the impact of smartphone use intensity on students' reading interest at SMAS DDI Babussalam Boddie Pangkep. This research uses a qualitative descriptive research method. Subject determination uses purposive sampling. Data collection techniques through observation, interviews, and documentation regarding smartphone use and students' reading interest. The data analysis technique is carried out in the form of qualitative analysis. The results showed that students were allowed to use smartphones at school by following the rules of use, for example only as a learning medium. The positive impacts of using smartphones include: accessing a large number of reading sources, increasing students' interest in reading, and accessing reading quickly and easily. Meanwhile, the negative impacts are eliminating interest in reading books in the library, lack of concentration on reading material, potential for misunderstanding the content of reading texts, and access to learning video content reducing students' interest in reading.